2012
DOI: 10.2174/1874917801205010001
|View full text |Cite
|
Sign up to set email alerts
|

Stalking, Intimate Partner Abuse, and the Police

Abstract: Stalking and intimate partner abuse (IPA) are two criminal problems that often come to the attention of the police. While there are many similarities between intimate partner stalking and IPA and many refer to intimate partner stalking as a variant of IPA (Logan, Leukefeld, and Walker, 2000), there may be differences in these cases, particularly at the point that they come to the attention of the police. These differences may have important implications for how the police respond and/or are able to respond. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 25 publications
5
17
1
Order By: Relevance
“…Second, previous stalking behavior was not a correlate of arrest (RQ2). This finding contradicts Melton’s (2012) study findings. One explanation may be the difference in measures used to operationalize stalking.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Second, previous stalking behavior was not a correlate of arrest (RQ2). This finding contradicts Melton’s (2012) study findings. One explanation may be the difference in measures used to operationalize stalking.…”
Section: Discussioncontrasting
confidence: 96%
“…First, results demonstrated that nearly one in five incidents, or 19.3% of the total incidents, included previous stalking (RQ1). This estimate falls in line with existing research among family violence incident reports from other police agencies (Melton, 2012; Tjaden & Thoennes, 2000). The IPV case file data used for the current study did not have a formal indicator for stalking behaviors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study found that when officers identified stalking behaviors in DV complaints, arrests for stalking were likely to follow. Indeed, of the cases in which officers identified stalking behaviors (40.9%, n ¼ 94), 62% resulted in an arrest for stalking (see Figure 1), which is substantially larger than arrest estimates established in prior studies (Melton, 2012;Tjaden & Thoennes, 2000;Woodroof, 2010). While this estimate is not based on a random sample of all DV complaints in RI, it provides a strong starting point to explore how officers handle stalking complaints.…”
Section: Discussionmentioning
confidence: 70%
“…Bukhari [2010], strongly protested that the structure of the state, state law and the courts are far away from being unbiased, and because of their close linkage to culture and custom, reflect the leading ideology of the time. Historically, Intimate Partner Abuse was viewed as a private matter in which the Criminal Justice System had little interest and took no action unless the violence resulted in serious injury or death [Melton, 2012]. Letourneau et al [2012] discovered from their findings that mothers affected by domestic violence are confronted with negative attitudes and ineffectual practices within convoluted bureaucratic Criminal Justice System, leaving many feeling re-victim.…”
Section: Causes Of Intimate Partner Violencementioning
confidence: 99%